Corporate Social Responsibility and financial performance among listed commercial banks in Sri Lanka: Is CSR a cost or profit driver? - Jeewanthi, H.A.C.; Ilma, F.S.F.; Jeewantha, G.K.C. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
Corporations are increasingly moving towards integrating corporate social responsibility (CSR) in their corporate planning to gain competitive advantages. Although there are many studies on the relationship between CSR and financial performance in diverse contexts, the literature is still limited, particularly for emerging economies. This paper investigates the relationship between CSR and financial performance in Sri Lanka. This is a quantitative study, and the correlational design was adopted to conduct it. Secondary data were collected from annual reports of all commercial banks listed on the Colombo Stock Exchange for the period 2013–2018.
Keywords: Corporate social responsibility, financial performance, bank size, bank age, listed commercial banks, competitive advantages